A carbon composite material, a highly reinforced rubber material, and a preparation method and application thereof
By combining adjacent bihydroxy polymer with carbon material, the problem of poor dispersion of carbon nanotubes and graphene in rubber is solved, and the mechanical properties and thermal conductivity of rubber are improved. It is suitable for applications such as rubber tires.
Patent Information
- Application Number
- CN202110610848.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-06-01
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-06-01
AI Technical Summary
The dispersion of carbon nanotubes and graphene in rubber is poor, resulting in a decrease in mechanical properties. The existing modification methods are costly and have high environmental pressure, and the reinforcement effect is not good.
A composite material adjacent to bihydroxy polymer and carbon material is used to form a π-π conjugation effect by combining with hydroxyl groups and carboxyl groups on carbon materials such as carbon nanotubes and graphene, thereby improving dispersion and enhancing the reinforcement performance of rubber.
It significantly improves the dispersion and mechanical properties of carbon composite materials in rubber, enhances the reinforcement and thermal conductivity of rubber, and is suitable for use in rubber tires and other applications.
Smart Images

Figure CN115433396B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rubber products, and in particular relates to a carbon composite material, a high-reinforcement rubber material, and a preparation method and application thereof. Background Art
[0002] Carbon materials such as carbon nanotubes and graphene are low-dimensional nanomaterials with excellent physical and mechanical properties. They have very large aspect ratios or specific surface areas, so they excel in mechanical, electrical and thermal conductivity, and are widely used in catalyst carriers, rubber-plastic composites, electrochemical materials, photoelectric sensors and other fields. At the same time, the above-mentioned carbon materials are easy to agglomerate due to their large aspect ratios and large specific surface areas, and have poor dispersion in the rubber matrix. They often form visible agglomerates in the rubber, causing the mechanical properties of rubber products to decrease significantly. For example, when used in rubber tires, it is difficult for carbon nanotubes and rubber molecules to form an effective bond, which causes the filler to generate more heat during driving and the rolling resistance cannot be ideally controlled.
[0003] In order to overcome the above difficulties, the industry often uses strong acid oxidation, grafting modification and other means to improve the surface function of carbon materials and increase their dispersibility in rubber. However, this method has a high application cost and great environmental pressure, especially the reinforcement effect is lower than expected. Summary of the invention
[0004] The present invention provides a carbon composite material, wherein the composite material comprises a contiguous dihydroxy polymer and a carbon material, wherein the contiguous dihydroxy polymer comprises structural units represented by formula (I), formula (II), formula (III), formula (IV) and formula (V):
[0005]
[0006] In formula (I) to formula (IV), R1, R2, R3, R4, R5 and R6 are the same or different and are independently selected from H, C 1-8 Alkyl; a, b, c and d are independently an integer greater than or equal to 0, and a and c are not 0 at the same time;
[0007] In formula (V), R 19 is selected from unsubstituted or optionally substituted with one, two or more R c Substituted aryl; each R c The same or different, independently selected from C 1-12 Alkyl; e is an integer greater than or equal to 0.
[0008] According to an embodiment of the present invention, the number average molecular weight of the adjacent dihydroxy polymer is 2,000 to 100,000.
[0009] Preferably, in the adjacent dihydroxy polymer, a is an integer between 0 and 2000, and a and c are not 0 at the same time; preferably, a is an integer between 50 and 1000.
[0010] Preferably, in the adjacent dihydroxy polymer, b is an integer between 0 and 200.
[0011] Preferably, in the adjacent dihydroxy polymer, c is an integer between 0 and 2000, and a and c are not 0 at the same time.
[0012] Preferably, in the adjacent dihydroxy polymer, d is an integer between 0 and 100.
[0013] Preferably, in the adjacent dihydroxy polymer, e is an integer between 0 and 2000.
[0014] Preferably, in the adjacent dihydroxy polymer, (a+c) / (a+b+c+d)≥0.5.
[0015] Preferably, in the adjacent dihydroxy polymer, the range of (a+c) / (a+b+c+d) is selected from 0.6 to 1.0.
[0016] Preferably, in the adjacent dihydroxy polymer, e / (a+b+c+d) is selected from 0 to 5.0.
[0017] According to an embodiment of the present invention, the carbon material is selected from at least one of carbon-based materials such as graphene, graphene oxide, carbon-supported graphene, fullerene, carbon nanotubes, vapor grown carbon fiber (VGCF), carbon nanohorns, carbon nanocoils, cup-stacked carbon nanotubes, bamboo-shaped carbon nanotubes and functionalized derivatives thereof, and is preferably at least one of graphene, graphene oxide, carbon nanotubes, carbon-supported graphene and functionalized derivatives thereof.
[0018] Preferably, the carbon material is carbon nanotubes.
[0019] The present invention also provides a method for preparing the carbon composite material, which comprises the following steps: mixing the carbon material and the adjacent dihydroxy polymer to obtain the carbon composite material.
[0020] According to an embodiment of the present invention, the method for preparing the above carbon composite material specifically comprises the following steps:
[0021] 1) first dissolving the adjacent dihydroxy polymer in an organic solvent, then adding carbon material powder and dispersing to obtain a mixture slurry;
[0022] Alternatively, the carbon material powder is first dispersed in an organic solvent, and then the adjacent dihydroxy polymer is added and dissolved to obtain a mixture slurry;
[0023] Alternatively, the carbon material powder and the adjacent dihydroxy polymer are added into an organic solvent, dispersed and dissolved to obtain a mixture slurry;
[0024] 2) adding water to separate the mixture slurry of step 1), and collecting the solid precipitate at the lower layer;
[0025] 3) The solid precipitate of step 2) is dried to obtain the carbon composite material.
[0026] Preferably, the organic solvent in step 1) is selected from at least one of alcohol, ketone, amide, sulfone, sulfoxide, furan, tetrahydrofuran, etc. The organic solvent is preferably at least one of N-methylpyrrolidone, ethanol, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, etc.
[0027] Preferably, in the mixture slurry of step 1), the concentration of the adjacent dihydroxy polymer is 0.1 wt% to 30 wt%, preferably 2 wt% to 15 wt%.
[0028] Preferably, in step 1), the mass ratio of the carbon material to the adjacent dihydroxy polymer is 1:(0.01-1), preferably 1:(0.05-0.1).
[0029] Preferably, in step 2), the mass ratio of water to the mixture slurry is (1-10): 1. Preferably, the water refers to pure water.
[0030] The present invention also provides the use of the carbon composite material in the field of rubber. Preferably, the rubber is a highly reinforced rubber material.
[0031] The present invention provides a rubber composition, which comprises the carbon composite material and rubber.
[0032] According to an embodiment of the present invention, the rubber composition comprises, by weight, 0.5 to 10 parts of the carbon composite material and 100 parts of rubber. Preferably, the rubber composition comprises: 0.5 to 5 parts of the carbon composite material and 100 parts of rubber, for example, the rubber composition comprises: 1 part of the carbon composite material and 100 parts of rubber.
[0033] Preferably, the rubber is at least one of natural rubber, styrene-butadiene rubber, chloroprene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, butyl rubber, halogenated butyl rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-vinyl acetate rubber, polyurethane rubber, eucommia gum, gutta-percha, fluororubber, silicone rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butadiene-styrene thermoplastic elastomer, butadiene-styrene-acrylonitrile thermoplastic elastomer, and ethylene-propylene-acrylate thermoplastic elastomer, or a mixture thereof.
[0034] Preferably, the rubber composition further comprises a vulcanizing agent.
[0035] Preferably, the rubber composition further comprises auxiliary materials. Preferably, the auxiliary materials are selected from at least one of antioxidants, plasticizers, vulcanization accelerators and activators.
[0036] Illustratively, the rubber composition includes, by weight: 1 part of the above-mentioned carbon composite material, 100 parts of natural rubber, 40 parts of carbon black, 2.5 parts of zinc oxide, 1.5 parts of stearic acid, 1.5 parts of accelerator, 1.5 parts of antioxidant, and 1.0 part of sulfur.
[0037] The present invention also provides a rubber material, which is prepared by mixing the rubber composition.
[0038] The present invention provides a method for preparing the above-mentioned rubber material, especially a highly reinforced rubber material. The preparation method comprises: adding various components in the above-mentioned rubber composition, mixing, and obtaining the rubber material.
[0039] According to an embodiment of the present invention, the method for preparing the rubber material specifically comprises: adding the components in the rubber composition, kneading, and then performing a vulcanization treatment to obtain the rubber material.
[0040] Exemplarily, the vulcanization treatment conditions are: vulcanization temperature 140-200° C., vulcanization time 5-60 min.
[0041] The present invention also provides an application of the rubber, preferably in a rubber tire.
[0042] The beneficial effects of the present invention are:
[0043] 1. The adjacent dihydroxy polymer has a multi-hydroxy structure, which can effectively combine with hydroxyl groups, carboxyl groups and other groups on carbon materials such as carbon nanotubes, graphene, and graphene oxide; further, the polymer can also have an aromatic group, which can produce a π-π conjugation effect with the unique long-range π bond of the carbon material; at the same time, the adjacent dihydroxy polymer has good compatibility with rubber. Experiments have shown that the carbon composite material of the present invention is added to rubber with excellent dispersibility, and can make full use of the excellent high reinforcement performance of the carbon material to enhance the reinforcement of the rubber.
[0044] 2. The rubber material prepared by the present invention not only has enhanced reinforcement, but also has improved tear strength, tensile strength and thermal conductivity, and is suitable for application in rubber tires. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a SEM image of the carbon composite material product of Preparation Example 3, with a magnification of 30,000 times.
[0046] Figure 2 This is a SEM image of the carbon composite material product of Preparation Example 10, with a magnification of 1500 times. DETAILED DESCRIPTION
[0047] The so-called "adjacent dihydroxyl groups" in the present invention, as shown in formula (I), means that one hydroxyl group is connected to each of two adjacent carbon atoms in the polymer main chain, and the polymer main chain contains multiple such structural units; or, as shown in formula (III), means that one hydroxyl group is connected to each of two adjacent carbon atoms in the polymer side chain, and the polymer side chain contains multiple such structural units.
[0048] [Carbon composite materials]
[0049] The present invention provides a carbon composite material, which comprises an adjacent dihydroxy polymer and a carbon material; the adjacent dihydroxy polymer comprises structural units represented by formula (I), formula (II), formula (III), formula (IV) and formula (V):
[0050]
[0051] In formula (I) to formula (IV), R1, R2, R3, R4, R5 and R6 are the same or different and are independently selected from H, C 1-8 Alkyl; a, b, c and d are independently an integer greater than or equal to 0, and a and c are not 0 at the same time;
[0052] In formula (V), R 19 is selected from unsubstituted or optionally substituted with one, two or more R c Substituted aryl; each R c The same or different, independently selected from C 1-12 Alkyl; e is an integer greater than or equal to 0.
[0053] For example, in formula (V), R 19 is selected from unsubstituted or optionally substituted with one, two or more R c Substituted C 6-20 Aryl; each R c The same or different, independently selected from C 1-12 Alkyl; For example, R 19 is selected from phenyl, 2-tolyl, 3-tolyl, 4-tolyl, 2-ethylphenyl, 3-ethylphenyl or 4-ethylphenyl.
[0054] For example, in the adjacent dihydroxy polymer, a is an integer between 0 and 2000, and a and c are not simultaneously 0. Preferably, a is an integer between 50 and 1000.
[0055] Illustratively, in the adjacent dihydroxy polymer, b is an integer between 0 and 200, for example, 1, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190 or 200.
[0056] Illustratively, in the adjacent dihydroxy polymer, c is an integer between 0 and 2000, and a and c are not simultaneously 0; for example, 1, 10, 100, 200, 300, 500, 800, 900, 1000, 1200, 1400, 1600, 1800 or 2000.
[0057] Illustratively, in the adjacent dihydroxy polymer, d is an integer between 0 and 100, for example, 1, 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100.
[0058] Illustratively, in the adjacent dihydroxy polymer, e is an integer between 0 and 2000, for example, 1, 10, 100, 200, 300, 500, 800, 900, 1000, 1200, 1400, 1600, 1800 or 2000.
[0059] Exemplarily, in the adjacent dihydroxy polymer, (a+c) / (a+b+c+d)≥0.5. Preferably, the range of (a+c) / (a+b+c+d) is selected from 0.6 to 1.0. For example, (a+c) / (a+b+c+d) is selected from 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 0.96, 0.97, 0.98, 0.99 or the range between any two of the above values.
[0060] Exemplarily, in the adjacent dihydroxy polymer, e / (a+b+c+d) is selected from 0 to 5.0, for example, 0, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.2, 1.5, 1.8, 2.0, 2.1, 2.4, 2.7, 3.0, 4.0, 5.0 or a range between any two of the above values.
[0061] The applicant has found through research that when a, b, c, d and e are selected within the above ranges, the carbon composite material prepared from the adjacent dihydroxy polymer and the carbon material is more suitable for application in rubber tires.
[0062] According to the present invention, the carbon material is selected from at least one of carbon-based materials such as graphene, graphene oxide, carbon-supported graphene, fullerene, carbon nanotubes, vapor grown carbon fibers (VGCF), carbon nanohorns, carbon nanocoils, cup-stacked carbon nanotubes, bamboo-shaped carbon nanotubes and functionalized derivatives thereof, and is preferably at least one of graphene, graphene oxide, carbon nanotubes, carbon-supported graphene and functionalized derivatives thereof.
[0063] According to a specific embodiment of the present invention, the carbon material is preferably carbon nanotubes.
[0064] According to the present invention, the number average molecular weight of the adjacent dihydroxy polymer is 2000-100000, for example, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 16000, 30000, 50000, 70000, 90000 or 100000.
[0065] According to the present invention, the above-mentioned adjacent dihydroxy polymer is prepared by a method comprising the following steps:
[0066] (i) preparing an epoxidized polymer by oxidation of a polymer containing a structural unit represented by formula (VI),
[0067]
[0068] In formula (VI), x=a+b, y=c+d, m+n=e; R1, R2, R3, R4, R5, R6, a, b, c, d and e are as defined above; m and n are integers greater than or equal to 0;
[0069] (ii) hydrolyzing the epoxidized polymer to obtain the contiguous bishydroxy polymer.
[0070] In step (i), the polymer containing the structural unit represented by formula (VI) can be obtained by polymerizing a conjugated diene monomer, wherein the conjugated diene monomer is selected from (R1)(R5)C=C(R2)-C(R3)=C(R4)(R6), and the definitions of R1, R2, R3, R4, R5, and R6 are as described above.
[0071] In step (i), the polymer containing the structural unit represented by formula (VI) can be prepared by reacting a conjugated diene monomer with R 19 -CH=CH2 is obtained by copolymerization of the structural monomers, R 19 The definition of is as described above; the conjugated diene monomer is selected from (R1)(R5)C=C(R2)-C(R3)=C(R4)(R6), and the definitions of R1, R2, R3, R4, R5, and R6 are as described above.
[0072] For example, the conjugated diene monomer may be 1,3-butadiene, 1,3-pentadiene or isoprene.
[0073] For example, R 19 The structural monomer represented by -CH=CH2 is selected from styrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene or 4-ethylstyrene.
[0074] Specifically, the preparation method of the polymer containing formula (VI) is as follows:
[0075] Conjugated diene polymer: a conjugated diene is mixed with a solvent (such as cyclohexane), and a catalyst (such as a three-component catalyst of nickel cyclohexaneate-boron trifluoride ether complex-triisobutylaluminum) is added to catalyze polymerization to prepare a polymer containing the structural unit described in formula (VI);
[0076] Alternatively, the conjugated diene and R 19 -CH=CH2 structure monomer block copolymer: quantitative R 19 -CH=CH2 structure monomer (R 19 The definition is as described above) is mixed with a solvent (such as an alkane, an aromatic hydrocarbon or a mixture of the two, such as cyclohexane), and a catalyst (such as sec-butyl lithium) is added at 30-65°C for catalytic reaction; then a certain amount of conjugated diene (such as 1,3-butadiene, 1,3-pentadiene or isoprene) is added for reaction; in the third step, R 19 -CH=CH2 is polymerized to prepare a polymer containing the structural unit of formula (VI);
[0077] Alternatively, the conjugated diene and R 19 -CH=CH2 structure monomer random copolymer: R 19 The structural monomer represented by -CH=CH2 and the conjugated diene are mixed with a solvent (such as cyclohexane), and a catalyst (such as sec-butyl lithium) is added for catalytic polymerization to prepare a polymer containing the structural unit described in formula (VI).
[0078] In step (i), the oxidation reaction includes but is not limited to the chlorohydrin method, the peroxide epoxidation method or the oxygen direct oxidation method. The oxidation reaction is an epoxidation reaction, and the oxidation reaction can be partial epoxidation or full epoxidation.
[0079] Illustratively, the peroxide can be a mixture of one or more of hydrogen peroxide, performic acid, peracetic acid, perbenzoic acid, meta-chloroperbenzoic acid, tert-butyl hydroperoxide, etc.
[0080] For example, the oxidation reaction can be carried out in an organic solvent containing a polymer or in a water / organic solvent emulsion, wherein the organic solvent includes but is not limited to aliphatic alkanes, halogenated aliphatic hydrocarbons, aromatic hydrocarbons, cycloalkanes, solvent oils, etc., preferably hexane, cyclohexane, heptane, dichloromethane, benzene, toluene, solvent oils, etc. The temperature of the oxidation reaction is 0 to 120° C., preferably 20 to 80° C.
[0081] In step (ii), the hydrolysis can be carried out by hydrolyzing the epoxidized polymer with a conventional acidic substance or alkaline substance to open the epoxy ring to obtain a polymer containing ortho-dihydroxyl groups on the CC chain. Exemplarily, the acidic substance includes inorganic acids such as aqueous hydrogen halide solution, sulfuric acid, and nitric acid; organic acids such as alkyl sulfonic acid; solid acids; heteropoly acids, etc.
[0082] For example, the hydrolysis reaction can be carried out in an organic solvent containing a polymer or in a water / organic solvent emulsion, wherein the organic solvent includes but is not limited to aliphatic alkanes, halogenated aliphatic hydrocarbons, aromatic hydrocarbons, cycloalkanes, solvent oils, cyclic ether compounds, sulfoxides, sulfones, pyrrolidone, methylpyrrolidone, etc., preferably tetrahydrofuran, dimethyl sulfoxide, methylpyrrolidone, etc. The temperature of the hydrolysis reaction is -20 to 150°C, preferably -10 to 80°C.
[0083] [Method for preparing carbon composite material]
[0084] The present invention provides a method for preparing the carbon composite material, comprising the following steps: mixing the carbon material and the adjacent dihydroxy polymer to obtain the carbon composite material.
[0085] In the present invention, the carbon material is selected as described above.
[0086] According to the present invention, the method for preparing the above carbon composite material specifically comprises the following steps:
[0087] 1) first dissolving the adjacent dihydroxy polymer in an organic solvent, then adding carbon material powder and dispersing to obtain a mixture slurry;
[0088] Alternatively, the carbon material powder is first dispersed in an organic solvent, and then the adjacent dihydroxy polymer is added and dissolved to obtain a mixture slurry;
[0089] Alternatively, the carbon material powder and the adjacent dihydroxy polymer are added into an organic solvent, dispersed and dissolved to obtain a mixture slurry;
[0090] 2) adding water to separate the mixture slurry of step 1), and collecting the solid precipitate at the lower layer;
[0091] 3) The solid precipitate of step 2) is dried to obtain the carbon composite material.
[0092] According to the present invention, in step 1), the organic solvent is selected from at least one of alcohol, ketone, amide, sulfone, sulfoxide, furan, tetrahydrofuran, etc. The organic solvent is preferably at least one of N-methylpyrrolidone, ethanol, dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, etc.
[0093] According to the present invention, in the mixture slurry of step 1), the concentration of the adjacent dihydroxy polymer is 0.1wt% to 30wt%, preferably 2wt% to 15wt%, for example 0.1, 0.5, 1.0, 2.0, 5.0, 10.0, 15.0, 20.0, 25.0 or 30.0wt%.
[0094] According to the present invention, in step 1), the mass ratio of the carbon material to the adjacent dihydroxy polymer is 1:(0.01-1), preferably 1:(0.05-0.1), for example, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1, 1:0.2, 1:0.4, 1:0.6, 1:0.8 or 1:1.0.
[0095] According to the present invention, in step 1), the dispersion is carried out under ultrasound and / or mechanical stirring.
[0096] According to the present invention, in step 1), the mixture slurry is a homogeneous mixture slurry, which means that the liquid is left standing for more than or equal to 1 day without precipitation, for example, for more than or equal to 10 days without precipitation.
[0097] According to the present invention, in step 2), the mass ratio of water to the mixture solution is (1-10): 1. Preferably, the water refers to pure water. Preferably, in step 2), the water is added multiple times, for example, added in 2 equal portions.
[0098] According to the present invention, in step 3), the drying is selected from any drying method such as freeze drying, spray drying, vacuum drum drying, etc.
[0099] [application]
[0100] The present invention also provides an application of the carbon composite material in the rubber field.
[0101] In a specific embodiment of the present invention, the rubber is preferably a highly reinforced rubber material.
[0102] [Rubber composition and rubber material]
[0103] The present invention also provides a rubber composition, which comprises the carbon composite material and rubber.
[0104] According to the present invention, the rubber composition comprises, by weight, 0.5 to 10 parts of the carbon composite material and 100 parts of rubber. Preferably, the rubber composition comprises: 0.5 to 5 parts of the carbon composite material and 100 parts of rubber, for example, the rubber composition comprises: 1 part of the carbon composite material and 100 parts of rubber.
[0105] According to the present invention, the rubber is at least one of natural rubber, styrene-butadiene rubber, chloroprene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, butyl rubber, halogenated butyl rubber, nitrile rubber, hydrogenated nitrile rubber, chloroprene rubber, ethylene-vinyl acetate rubber, polyurethane rubber, eucommia gum, gutta-percha, fluororubber, silicone rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butadiene-styrene thermoplastic elastomer, butadiene-styrene-acrylonitrile thermoplastic elastomer, and ethylene-propylene-acrylate thermoplastic elastomer, or a mixture thereof.
[0106] The rubber composition also includes a vulcanizing agent.
[0107] According to the present invention, the vulcanizing agent is selected from, for example, sulfur, metal oxides, resin vulcanizing agents, thiuram, and peroxides, preferably sulfur.
[0108] According to the present invention, the rubber composition further comprises auxiliary materials.
[0109] According to the present invention, the auxiliary materials can be selected from the auxiliary materials commonly used in the technical field, as long as the highly reinforced rubber material of the present invention can be obtained. For example, the auxiliary materials are selected from at least one of carbon black, antioxidant, plasticizer, vulcanization accelerator, and activator. Preferably, the plasticizer includes at least one of aromatic oil, cycloalkane oil, paraffin oil, C5, C9, plant resin, and stearic acid, preferably stearic acid. Preferably, the activator is selected from zinc oxide.
[0110] According to a specific embodiment of the present invention, the rubber composition includes, by weight, 1 part of the above-mentioned carbon composite material, 100 parts of natural rubber, 40 parts of carbon black, 2.5 parts of zinc oxide, 1.5 parts of stearic acid, 1.5 parts of vulcanization accelerator, 1.5 parts of antioxidant, and 1.0 part of sulfur.
[0111] The invention also provides a rubber material, which is prepared by mixing the rubber composition.
[0112] [Method for preparing rubber material]
[0113] The present invention also provides a method for preparing the rubber material, especially the highly reinforced rubber material. The method comprises: adding the components in the rubber composition, mixing and kneading to obtain the rubber material.
[0114] In a specific embodiment of the present invention, the method for preparing the rubber material specifically comprises: adding the components in the rubber composition, kneading, and then performing a vulcanization treatment to obtain the rubber material.
[0115] The present invention does not impose any specific limitation on the mixing and vulcanization treatment, and the mixing and vulcanization treatment may be carried out under conventional process conditions in the technical field, as long as a rubber material that meets the performance requirements can be obtained.
[0116] In a specific embodiment of the present invention, the mixing is carried out in an internal mixer or an open mixer.
[0117] In a specific embodiment of the present invention, the mixing is first performed in an internal mixer and then in an open mixer.
[0118] In a specific embodiment of the present invention, the vulcanization treatment conditions are: vulcanization temperature 140-200° C., vulcanization time 5-60 min.
[0119] [Application of rubber materials]
[0120] The present invention also provides an application of the rubber material, preferably in a rubber tire.
[0121] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0122] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0123] The test in the embodiment of the present invention mainly adopts the following equipment:
[0124] Material structure test 1 H-NMR, 13 C-NMR used a JOEL 600 MHz pulse Fourier transform NMR spectrometer;
[0125] The polymer molecular weight was tested by Aglilent's PL-GPC50 (equipped with a differential refractometer and an evaporative light scattering detector); the scanning electron microscope was a JCM-7000 desktop scanning electron microscope produced by Japan Electronics Corporation; the Shore A hardness was tested by an XY-1 rubber hardness tester produced by Shanghai Machinery Plant No. 4; the tensile properties and tear strength were tested by an A17000 electronic tensile testing machine produced by Taiwan High Speed Rail Testing Company; and the thermal conductivity was tested by a DRL-5 thermal conductivity system tester produced by Xiangtan Xiangyi Instrument Co., Ltd.
[0126] Preparation Example 1
[0127] Preparation of adjacent dihydroxy polymer SBSOH:
[0128] The first step: synthesizing a block copolymer of styrene and butadiene SBS according to the method disclosed in Handbook of Synthetic Rubber Industry (edited by Zhao Xutao and Liu Dahua, second edition, Chemical Industry Press, 2006);
[0129] Step 2: using formic acid as a catalyst, dissolving the block copolymer SBS of styrene and butadiene prepared in the first step in a mixed solution of cyclohexane and ethylene dichloride, adding 30% hydrogen peroxide to the mixed solution, causing double bonds in the polymer molecular structure to undergo epoxidation reaction, thereby preparing an epoxidized polymer solution;
[0130] Step 3: Add 70% perchloric acid aqueous solution to the epoxidized polymer solution to open the epoxy group to adjacent dihydroxyl groups. The reactants are washed with water and dried to obtain the aromatic-containing polyhydroxy polymer SBSOH.
[0131] The number average molecular weight, e / (a+b+c+d), and (a+c) / (a+b+c+d) results of the SBSOH samples are shown in Table 1.
[0132] Table 1
[0133] SBSOH Number average molecular weight e / (a+b+c+d) (a+c) / (a+b+c+d) SBSOH-1 6700 3.0 0.70 SBSOH-2 14500 3.0 0.66 SBSOH-3 67700 1 0.60 SBSOH-4 92300 2.9 0.66
[0134] In Table 1, the ratios of a, b, c, d and e and (a+c) / (a+b+c+d) and e / (a+b+c+d) are given by 1 The H-NMR test results were obtained by calculation.
[0135] Preparation Example 2
[0136] Preparation of adjacent dihydroxy polymer PBOH:
[0137] The PBOH samples shown in Table 1 were prepared by using the above 1,3-butadiene as a raw material and referring to the method disclosed in Example 1 of CN110964131A.
[0138] The results of the number average molecular weight and number of repeating units of the PBOH samples are shown in Table 2.
[0139] Table 2
[0140]
[0141] In Table 2, a, b, c, d and the ratios of (a+c) / (a+b+c+d) and a / c are given by 1 The H-NMR test results were obtained by calculation.
[0142] Preparation Example 3
[0143] Prepare 100 g of dimethyl sulfoxide solution containing 5.0 wt% of adjacent bishydroxy polymer SBSOH-1, add 50.0 g of carbon nanotubes (tube diameter 10-20 nm, tube length 20-30 μm) into the above solution, and ultrasonicate for 30 minutes to obtain a uniform black mixture slurry.
[0144] While stirring, pour the mixture slurry into 500 ml of pure water to obtain a precipitation layer and a water layer containing dimethyl sulfoxide. After ultrasonic treatment for 60 minutes, the upper water layer is decanted; 500 ml of pure water is added to the precipitation layer again, and ultrasonic treatment is performed for another 30 minutes to separate a wet solid precipitation layer. The wet solid precipitation layer is placed in a flask and vacuum-dried at 60°C to remove moisture, thereby obtaining 55 g of black carbon nanocomposite powder.
[0145] The 30000 times scanning electron microscope image of the carbon composite material of this preparation example is shown in Figure 1 .Depend on Figure 1 It can be seen that the carbon nanotubes are not agglomerated, and the rough part of the carbon nanotube surface is the combined adjacent dihydroxy polymers.
[0146] Preparation Example 4
[0147] The preparation method of the carbon composite material in this preparation example is the same as that in Preparation Example 3, except that the adjacent dihydroxy polymer is SBSOH-2.
[0148] Preparation Example 5
[0149] The preparation method of the carbon composite material in this preparation example is the same as that in Preparation Example 3, except that the adjacent dihydroxy polymer is SBSOH-3.
[0150] Preparation Example 6
[0151] The preparation method of the carbon composite material in this preparation example is the same as that in Preparation Example 3, except that the adjacent dihydroxy polymer is SBSOH-4.
[0152] Preparation Example 7
[0153] The preparation method of the carbon composite material in this preparation example is the same as that in Preparation Example 3, except that the adjacent dihydroxy polymer is PBOH-1.
[0154] Preparation Example 8
[0155] The preparation method of the carbon composite material in this preparation example is the same as that in Preparation Example 3, except that the adjacent dihydroxy polymer is PBOH-2.
[0156] Preparation Example 9
[0157] The preparation method of the carbon composite material in this preparation example is the same as that in Preparation Example 3, except that the adjacent dihydroxy polymer is PBOH-3.
[0158] Preparation Example 10
[0159] The preparation method of the carbon composite material in this preparation example is the same as that in Preparation Example 3, except that the carbon nanotubes are replaced with graphene oxide (≤2 layers, thickness 0.55-1.1 nm, oxygen content 44 wt%).
[0160] The SEM image of the carbon composite material of this preparation example is shown in Figure 2 .Depend on Figure 2 It can be seen that the flake material is graphene oxide, and the adjacent dihydroxy polymer is uniformly attached to the graphene oxide.
[0161] Test Example 1
[0162] The black mixture slurry of Preparation Example 3-10 was placed at 25°C for 24 hours, and the mixture slurry did not separate; after being placed for 10 days, the mixture slurry still did not precipitate. However, the dimethyl sulfoxide solution of carbon nanotubes without the adjacent dihydroxy polymer was placed at 25°C for 10 hours, and separation or precipitation occurred. This shows that after adding the adjacent dihydroxy polymer, the carbon nanotubes are uniformly dispersed in the mixture slurry.
[0163] Example 1
[0164] 1 part by weight of the carbon composite material of Carbon Composite Material Preparation Example 3, 100 parts by weight of natural rubber, 40 parts by weight of carbon black, 2.5 parts by weight of zinc oxide, 1.5 parts by weight of stearic acid, 1.5 parts by weight of accelerator, 1.5 parts by weight of antioxidant, and 1.0 part by weight of sulfur are mixed evenly in an internal mixer and then in an open mixer, and then vulcanized at 150° C. for 20 minutes to obtain a highly reinforced rubber material with added carbon nanomaterial composite.
[0165] Example 2
[0166] The preparation method of the highly reinforced rubber material in this embodiment is the same as that in Embodiment 1, except that the carbon composite material is the product of Carbon Composite Material Preparation Example 4.
[0167] Example 3
[0168] The preparation method of the highly reinforced rubber material in this embodiment is the same as that in Embodiment 1, except that the carbon composite material is the product of Carbon Composite Material Preparation Example 5.
[0169] Example 4
[0170] The preparation method of the highly reinforced rubber material in this embodiment is the same as that in Embodiment 1, except that the carbon composite material is the product of Carbon Composite Material Preparation Example 6.
[0171] Example 5
[0172] The preparation method of the highly reinforced rubber material in this embodiment is the same as that in Embodiment 1, except that the carbon composite material is the product of Carbon Composite Material Preparation Example 7.
[0173] Example 6
[0174] The preparation method of the highly reinforced rubber material in this embodiment is the same as that in Embodiment 1, except that the carbon composite material is the product of Carbon Composite Material Preparation Example 8.
[0175] Example 7
[0176] The preparation method of the highly reinforced rubber material in this embodiment is the same as that in Embodiment 1, except that the carbon composite material is the product of Carbon Composite Material Preparation Example 9.
[0177] Example 8
[0178] The preparation method of the highly reinforced rubber material in this embodiment is the same as that in Embodiment 1, except that the carbon composite material is the product of Carbon Composite Material Preparation Example 10.
[0179] Comparative Example 1
[0180] The preparation method of the rubber material of this comparative example is the same as that of Example 1, except that, instead of adding the above-mentioned carbon composite material, 0.91 parts by weight of carbon nanotubes (tube diameter 10-20 nm, tube length 20-30 μm; the same amount of carbon nanotubes as contained in the carbon composite material of Example 1) are added.
[0181] Test Example 2
[0182] The highly reinforced rubber materials or rubber materials prepared in Examples 1-8 and Comparative Example 1 were tested for tensile strength, tensile elongation, Shore A hardness, tear strength, etc. The test methods were carried out according to the corresponding test methods in GB / T528-2009, GB / T529-2008 and GB / T531.1-2008, and the specific measured values are shown in Table 3.
[0183] Table 3
[0184]
[0185] From the experimental results in Table 3, it can be seen from the comparison of Examples 1-8 and the comparative example that the thermal conductivity and mechanical properties such as tensile strength and tear strength of the highly reinforced rubber material to which the carbon composite material of the present invention is added are significantly improved.
[0186] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A rubber composition, It is characterized in that In parts by weight, the rubber composition comprises: 0.5 to 10 parts of carbon composite material and 100 parts of rubber; The carbon composite material comprises a contiguous dihydroxy polymer and a carbon material; the contiguous dihydroxy polymer comprises structural units represented by formula (I), formula (II), formula (III), formula (IV) and formula (V): ; Formula (I) Formula (II); ; Formula (III) Formula (IV) Formula (V); In formula (I) to formula (IV), R 1 , R 2 , R 3 , R 4 , R 5 and R 6 The same or different, independently selected from H, C 1-8 Alkyl; a, b, c and d are independently an integer greater than or equal to 0, and a and c are not 0 at the same time; In formula (V), R 19 is selected from unsubstituted or optionally substituted with one, two or more R c Substituted aryl; each R c The same or different, independently selected from C 1-12 Alkyl; e is an integer greater than or equal to 0; In the adjacent dihydroxy polymer, (a+c) / (a+b+c+d)≥0.5; The carbon material is selected from at least one of graphene, graphene oxide, carbon-supported graphene, fullerene, carbon nanotube, vapor-grown carbon fiber, carbon nanohorn, carbon nanocoil and functionalized derivative carbon-based materials.
2. The rubber composition according to claim 1, It is characterized in that The number average molecular weight of the adjacent dihydroxy polymer is 2000-100000.
3. The rubber composition according to claim 1, It is characterized in that In the adjacent dihydroxy polymer, a is an integer between 0 and 2000, and a and c are not 0 at the same time; and / or, in the adjacent dihydroxy polymer, b is an integer between 0 and 200; And / or, in the adjacent dihydroxy polymer, c is an integer between 0 and 2000, and a and c are not 0 at the same time; and / or, in the adjacent dihydroxy polymer, d is an integer between 0 and 100; and / or, in the adjacent dihydroxy polymer, e is an integer between 0 and 2000; and / or, in the adjacent dihydroxy polymer, the range of (a+c) / (a+b+c+d) is selected from 0.6 to 1.0; And / or, in the adjacent dihydroxy polymer, e / (a+b+c+d) is selected from 0 to 5.
0.
4. The rubber composition according to claim 1, It is characterized in that a is an integer between 50 and 1000.
5. The rubber composition according to claim 1, It is characterized in that The carbon material is selected from at least one of graphene, graphene oxide, carbon nanotubes, carbon-supported graphene and functionalized derivatives thereof.
6. The rubber composition according to claim 1, It is characterized in that The carbon material is carbon nanotube.
7. The rubber composition according to claim 1, It is characterized in that The carbon composite material is prepared by a preparation method comprising the following steps: mixing the carbon material and the adjacent dihydroxy polymer to obtain the carbon composite material.
8. The rubber composition according to claim 7, It is characterized in that The preparation method specifically comprises the following steps: 1) first dissolving the adjacent dihydroxy polymer in an organic solvent, then adding carbon material powder and dispersing to obtain a mixture slurry; Alternatively, the carbon material powder is first dispersed in an organic solvent, and then the adjacent dihydroxy polymer is added and dissolved to obtain a mixture slurry; Alternatively, the carbon material powder and the adjacent dihydroxy polymer are added into an organic solvent, dispersed and dissolved to obtain a mixture slurry; 2) adding water to separate the mixture slurry in step 1), and collecting the solid precipitate in the lower layer; 3) The solid precipitate of step 2) is dried to obtain the carbon composite material.
9. The rubber composition according to claim 8, It is characterized in that In the mixture slurry of step 1), the concentration of adjacent dihydroxy polymer is 0.1wt% to 30wt%; In step 1), the mass ratio of the carbon material to the adjacent dihydroxy polymer is 1:(0.01~1).
10. The rubber composition according to claim 8, It is characterized in that In step 2), the mass ratio of water to the mixture is (1-10):
1.
11. The rubber composition according to claim 8, It is characterized in that In the mixture slurry of step 1), the concentration of adjacent dihydroxy polymer is 2wt% to 15wt%; In step 1), the mass ratio of the carbon material to the adjacent dihydroxy polymer is 1:(0.05~0.1).
12. The rubber composition according to claim 1, It is characterized in that The rubber is at least one of natural rubber, styrene-butadiene rubber, chloroprene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, butyl rubber, halogenated butyl rubber, nitrile rubber, hydrogenated nitrile rubber, ethylene-vinyl acetate rubber, polyurethane rubber, eucommia gum, gutta-percha, fluororubber, silicone rubber, chlorinated polyethylene rubber, chlorosulfonated polyethylene rubber, butadiene-styrene thermoplastic elastomer, butadiene-styrene-acrylonitrile thermoplastic elastomer, and ethylene-propylene-acrylate thermoplastic elastomer, or a mixture thereof.
13. The rubber composition according to claim 1, It is characterized in that The rubber composition also includes a vulcanizing agent.
14. The rubber composition according to claim 1, It is characterized in that The rubber composition also includes auxiliary materials; the auxiliary materials are selected from at least one of carbon black, antioxidant, plasticizer, vulcanization accelerator and activator.
15. A rubber material, It is characterized in that The rubber material is prepared by mixing the rubber composition according to any one of claims 1 to 14.
16. Use of the rubber material according to claim 15, It is characterized in that The rubber material is used for rubber tires.
Citation Information
Patent Citations
Polyhydroxy-containing polymer and preparation method and application thereof
CN110964131A
Composite comprising a metal component and a functional polymer matrix
CN108136836A
Rubber composition comprising a functional diene polymer
CN108137716A
Preparation method of bifunctional conjugated diene rubber
CN112442145A
Rubber composition comprising a polyphenolic compound
CN112739552A
